Melamine‐Based Metal‐Chelating Porous Organic Polymers for Efficient CO2 Capture and Conversion. Issue 37 (1st October 2018) - Tang, Feiying; Hou, Jianan; Liang, Kaixin; Huang, Jianhan; Liu, You‐Nian
Abstract : Due to their tailored porosity, high catalytic activity and excellent chemical/thermal stability, porous organic polymers and their metal complexes hold promising potential in CO2 capture and conversion. In this work, two kinds of melamine‐based porous polymers (TPAMP and TPBMP) and their zinc complexes (Zn‐TPAMP and Zn‐TPBMP) were synthesized. Zn‐TPAMP and Zn‐TPBMP present high CO2 uptake of 11.7 wt.‐% and 16.8 wt.‐% at 273 K and 1 bar, respectively. In particular, Zn‐TPAMP demonstrates high catalytic activity for the cycloaddition of CO2 with epoxides (TOF: 1383 h –1 ). The high CO2 uptake can be contributed to the dominant microporosity and N‐containing groups; while the high catalytic activity can be ascribed to the considerable mesopores and the introduction of zinc ions. In addition, the steric configuration of the two different building blocks leads to a significant difference in the porosity of the prepared polymers, which endow them with different performance for CO2 uptake and conversion. Our finding provides a new approach to the synthesis of metal‐chelating porous polymers for efficient CO2 capture and conversion. Abstract : Two kinds of melamine‐based porous polymers and their metal complexes were synthesized. The polymers and zinc complexes exhibit enhanced capacity of CO2 uptake and superior catalytic activity for the cycloaddition of CO2 with epoxides. This work provides a new approach to the synthesis of metal‐chelating porous polymers for highly efficient CO2 capture and conversion.